2019
DOI: 10.1186/s12937-019-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Food taboo among pregnant Ethiopian women: magnitude, drivers, and association with anemia

Abstract: BackgroundThere are pervasive pregnancy-related food taboos and myths (PRFT) in Ethiopia. The evidence, however, is limited on whether PRFT contributes to the burden of maternal anemia. Thus, this study was aimed to determine the magnitude of PRFT, the reasons for adherence to PRFT, and the association of adherence to PRFT with anemia, among pregnant Ethiopian women.MethodsThe study was case-control in design and recruited a sample of 592 pregnant women attending antenatal care in four health facilities in Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
2
32
1
6
Order By: Relevance
“…The main reasons for the restriction of the food items held as taboo in this study were, the fear that the food will be plastered on fetal head and having large baby which make labor and delivery di cult. This nding is supported by ndings from a study in Shashmane and Addis Ababa that state the reasons for adhering to pregnancy related food taboos and myths to be large baby and di cult birthing and 'food sticking' on the fetal head (5,14) .A study in Accra Ghana also showed that pregnant women were restricted from consuming certain foods to check their health, control the weight of the expectant mother and unborn child and ensure there is a safe delivery, which is consistent with our nding (7).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The main reasons for the restriction of the food items held as taboo in this study were, the fear that the food will be plastered on fetal head and having large baby which make labor and delivery di cult. This nding is supported by ndings from a study in Shashmane and Addis Ababa that state the reasons for adhering to pregnancy related food taboos and myths to be large baby and di cult birthing and 'food sticking' on the fetal head (5,14) .A study in Accra Ghana also showed that pregnant women were restricted from consuming certain foods to check their health, control the weight of the expectant mother and unborn child and ensure there is a safe delivery, which is consistent with our nding (7).…”
Section: Discussionmentioning
confidence: 74%
“…Attitude and beliefs of the pregnant women themselves towards the food taboos is another reason for the adherence to the food taboos. Similarly, a qualitative study conducted in Addis Ababa points that the underlying reasons for the adherence to pregnancy related food taboos and myths (PRFT) were largely traditionally held beliefs and misconceptions (14). The ndings have strong practical implication.…”
Section: Discussionmentioning
confidence: 99%
“…Food taboo prohibits eating certain food items most of which are nutritious, resulting in poor nutritional outcomes [17]. In Ethiopia, several studies reported the existence of pervasive pregnancy-related food taboos and myths, which might be contributing to the burden of maternal anemia in the country [18,19]. Ethiopian pregnant women avoid certain food items for a range of reasons; some associated with pregnancy outcome and birthing process and others to avoid undesirable aesthetic features in the baby [19].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the trend of adolescents' adherence to food taboo is getting weaker along time, avoiding eating of some available foods in resource limited settings, because for reasons related to foods taboo could signi cantly increase the risk of under-nutrition. Similar studies also recognized the effect of food taboo with nutritional problems [46][47][48], from a qualitative study explores that parental in uence on eating behaviors in the perspective of the family's culture or religions as well as their habit play an important role in in uencing food choice of adolescents [49]. In settings where food shortage is evident, presence of culturally backed food taboo among adolescents girls may implies that the relatively higher nutritional de ciency can persist.…”
Section: Discussionmentioning
confidence: 99%